Psychic threats and somatic shelters : attuning to the body in contemporary psychoanalytic dialogue - Yarom, Nitza, 1943- (Hove, East Sussex : Routledge, 2015)
"There is increasing recognition within psychoanalysis and related therapies that awareness of the body is important in understanding and treating patients. Psychic Threats and Somatic Shelters explores the ways in which adults and children become acquainted with the range of physical issues that arise within their psychoanalytic or psychological treatments. Nitza Yarom discusses in a practical and clinically focused way the large variety of physical outlets which today's person uses to shelter from the many troubles and restrictions that are placed on everyday life. Her book is divided into two main sections: Somatic shelters, which explores the variety of physical symptoms encountered by patients, including problems with weight and eating; with sensation through sight, sound, smell, and taste; in movement through hyper-activity or rigidity; and through the communication of physical pain. Embodied dialogue, in which the author updates the use of the basic technical principles of psychoanalysis to involve the body in the treatment including transference and counter-transference between analyst and patient. In Psychic Threats and Somatic Shelters the emotional communication of these body narratives are vividly demonstrated in the treatments presented, here the interaction in the consulting room is revealed in bodily resonance and its therapeutic effects. This book is written for psychoanalysts and psychotherapists, psychologists, body therapists, family therapists, social workers, and art/movement therapists."--Page 4 of cover
Includes bibliographical references (pages 205-206) and index.
Keywords: Mind and body; Psychoanalysis; Psychotherapist and patient